Analysis Of Stunting Prevention From Upstream To Downstream In Indonesia - Marsalino Marsalino; Topik Hidayat (Jurnal Scientia, 2024)
This research aims to look at the upstream and downstream efforts to reduce stunting in Indonesia. Stunting is an urgent issue to be resolved because it has an impact on the quality of Indonesia's human resources in the future. Indonesia is a country with a high prevalence of stunting, namely around 36%. The government has made various efforts to tackle the problem of stunting through various policies and regulations as well as through a number of interventions, both specific and sensitive. The research method used is descriptive-qualitative analysis based on library research. The research results show that, at the upstream (policy level) there have been many government policies issued as an effort to accelerate stunting reduction, but in reality the stunting reduction rate is still far from the target. Downstream, there are still many communities and program implementers at the grassroots level who do not have adequate knowledge regarding stunting itself, both its impact, the factors that cause it, and how to overcome it. The community-based prevention system needs to be further improved, because high public awareness of the importance of balanced nutrition, sanitation and environmental cleanliness is a big asset to reduce stunting rates.